Structural changes in the sacroiliac joint on MRI and relationship to ASDAS inactive disease in axial spondyloarthritis: a 2-year study comparing treatment with etanercept in EMBARK to a contemporary control cohort in DESIR - Walter P. Maksymowych; Pascal Claudepierre; Manouk de Hooge; Robert G. Lambert; Robert Landewé; Anna Molto; Désirée van der Heijde; Jack F. Bukowski; Heather Jones; Ron Pedersen; Annette Szumski; Bonnie Vlahos; et al. (Arthritis Research & Therapy, 2021)
Abstract Background Limited information is available on the impact of treatment with a tumor necrosis factor inhibitor (TNFi) on structural lesions in patients with recent-onset axial spondyloarthritis (axSpA). We compared 2-year structural lesion changes on magnetic resonance imaging (MRI) in the sacroiliac joints (SIJ) of patients with recent-onset axSpA receiving etanercept in a clinical trial (EMBARK) to similar patients not receiving biologics in a cohort study (DESIR). We also evaluated the relationship between the Ankylosing Spondylitis Disease Activity Score (ASDAS) and change in MRI structural parameters. Methods The difference between etanercept (EMBARK) and control (DESIR) in the net percentage of patients with structural lesion change was determined using the SpondyloArthritis Research Consortium of Canada SIJ Structural Score, with and without adjustment for baseline covariates. The relationship between sustained ASDAS inactive disease, defined as the presence of ASDAS < 1.3 for at least 2 consecutive time points 6 months apart, and structural lesion change was evaluated. Results This study included 163 patients from the EMBARK trial and 76 from DESIR. The net percentage of patients with erosion decrease was significantly greater for etanercept vs control: unadjusted: 23.9% vs 5.3%; P = 0.01, adjusted: 23.1% vs 2.9%; P = 0.01. For the patients attaining sustained ASDAS inactive disease on etanercept, erosion decrease was evident in significantly more than erosion increase: 34/104 (32.7%) vs 5/104 (4.8%); P < 0.001. A higher proportion had erosion decrease and backfill increase than patients in other ASDAS status categories. However, the trend across ASDAS categories was not significant and decrease in erosion was observed even in patients without a sustained ASDAS response. Conclusions These data show that a greater proportion of patients achieved regression of erosion with versus without etanercept. However, the link between achieving sustained ASDAS inactive disease and structural lesion change on MRI could not be clearly established. Trial registration EMBARK: ClinicalTrials.gov identifier: NCT01258738 , Registered 13 December 2010; DESIR: ClinicalTrials.gov identifier: NCT01648907 , Registered 24 July 2012.